Xenotransplantation: Animal Organs Transplanted into Humans from The Perspectives of Islamic Jurisprudence and Legal Opinions - Muhammad Azizan Sabjan; Noor Shakirah Mat Akhir; Roshimah Shamsudin; Muhammad Ikhlas Rosele; Farah Salwani Muda @ Ismail; Halipah Hamzah (Universiti Sains Islam Malaysia, 2025)
Sains Insani, Volume 10 Issue 2 Page (139–150)